The Search for Transient Astrophysical Neutrino Emission With IceCube-DeepCore - Aartsen, M. G.; Abraham, K.; Ackermann, M.; Aguilar, J. A.; Adams, J.; Golup, Geraldina Tamara; Walck, C.; Wallace, A.; Wallraff, M.; Wandkowsky, N.; Weaver, Ch.; Wendt, C.; et al. (IOP Publishing, 2016)
Fil: Aartsen, M. G.. University of Adelaide; Australia